Exploring inequity factors in higher education: Promoting equitable access and success in the US - Aicha Adoui (SIMULACRA: JURNAL SOSIOLOGI, 2023)
The issue of equity in higher education has gained prominence as it has become increasingly clear that opportunities for higher education are not equitably distributed among different student groups. This paper provides a thorough understanding of the key components of equitable access and success in higher education, primarily in the context of the United States. It also seeks to explore the effectiveness of affirmative action, financial aid and scholarship systems, successful initiatives, cultural and sociological attitudes, and institutional structures and services in promoting equitable access and success in higher education. The paper uses a systematic review methodology to analyze academic and policy documents, program evaluations, and case studies. The analysis includes a synthesis of key findings and themes from the literature review, an examination of successful initiatives and programs in higher education institutions in the United States. The findings suggest that while affirmative action and financial aid programs have been successful in promoting equitable access and success in higher education, further efforts are needed to address cultural and societal attitudes that perpetuate inequities in higher education. Recommendations for future research include the long-term effects of financial aid and cultural barriers to building a more equitable education.